Pelaksanaan Pasar Lelang Komoditas di Provinsi Sumatera Utara - Fadillah Hanum; Nuri Aslami (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The auction market is a trading system in which buyers compete with other buyers and sellers compete with other sellers to achieve the most profitable price in the same place. Market auctions are an effective way in the trading system through transparency in pricing mechanisms, increasing incentives to increase production and quality. This auction market is also able to help cut long chains. With the government's auction market, it facilitates sellers/farmers (producers) and buyers (consumers) to meet in one place without intermediaries (distributors) thus smoothing the trade chain. To improve the quality of market auctions, an analysis of the process of organizing commodity auction markets carried out by the North Sumatra Regional Department of Industry and Trade is needed. By analyzing the auction market, the implementation process is carried out by the North Sumatra Province Industry and Trade Service in accordance with the Decree of the Minister of Industry and Trade of the Republic of Indonesia No. 650 of 2004.Â